The scientific basis, some results, and perspectives of modeling evolutionarily conditioned noogenesis of artificial creatures in virtual biocenoses. - Zachepylo, Mykhailo Oleksandrovych; Yushchenko, Oleksandr Heorhiiovych (Національний технічний університет "Харківський політехнічний інститут", 2023)
This research aimed to gain a profound understanding of virtual biocenoses intricate digital ecosystems, with the goal of elucidating and replicating the emergence and evolution of intelligence in artificial creatures – referred to as noogenesis. A comprehensive analysis of existing studies within virtual biocenoses was undertaken to glean valuable insights into the complexities of modeling dynamic ecosystems where artificial agents engaged in intricate interactions. The pivotal role of neural networks in shaping the adaptive behaviors of artificial creatures within these environments was underscored. A meticulous investigation into neural networks' evolution methodologies revealed the evolution of their architecture complexity over time, culminating in the facilitation of flexible and intelligent behaviors. However, a lack of study existed in the domain of nurturing evolutionary-based communication and cooperation capabilities within virtual biocenoses. In response to this gap, a model was introduced and substantiated through simulation experiments. The simulation results vividly illustrated the model's remarkable capacity to engender adaptive creatures endowed with the capability to efficiently respond to dynamic environmental changes. These adaptive entities displayed efficient optimization of energy consumption and resource acquisition. Moreover, they manifested both intellectual and physical transformations attributed to the evolution and encoding principles inspired by the NeuroEvolution of Augmented Topologies. Significantly, it became apparent that the evolutionary processes intrinsic to the model were inextricably linked to the environment itself, thus harmonizing seamlessly with the overarching goal of this research. Future research directions in this field were outlined. These pathways provided a foundation for further exploration into the evolution of artificial creatures in virtual biocenoses and the emergence of advanced communication and cooperation capabilities. These advancements hold the potential to move artificial life and artificial intelligence to new levels of understanding and capability.

Це дослідження мало на меті отримати глибоке розуміння складних цифрових екосистем віртуальних біоценозів з метою з'ясувати та відтворити появу та еволюцію інтелекту в штучних створінь, що називається ноогенезом. Було проведено комплексний аналіз існуючих досліджень у віртуальних біоценозах, щоб отримати цінну інформацію про складність моделювання динамічних екосистем, де штучні створіння беруть участь у комплексній взаємодії. Було підкреслено ключову роль нейронних мереж у формуванні адаптивної поведінки штучних створінь у цих середовищах. Ретельне дослідження методології еволюції нейронних мереж виявило еволюцію складності їхньої архітектури з часом, кульмінацією якої стало сприяння гнучкій та інтелектуальній поведінці. Однак існував брак досліджень у сфері розвитку еволюційних можливостей спілкування та співпраці у віртуальних біоценозах. У відповідь на цю прогалину була введена модель та обґрунтована шляхом імітаційних експериментів. Результати моделювання яскраво проілюстрували дивовижну здатність моделі породжувати адаптивних істот, наділених здатністю ефективно реагувати на динамічні зміни навколишнього середовища. Ці адаптивні штучні істоти показали ефективну оптимізацію споживання енергії та отримання ресурсів. Крім того, вони продемонстрували як інтелектуальні, так і фізичні трансформації, пов'язані з принципами еволюції та кодування, натхненними нейроеволюцією доповнених топологій. Важливо, що стало очевидним, що еволюційні процеси, властиві моделі, були нерозривно пов'язані з самим середовищем, таким чином бездоганно узгоджуючись із головною метою цього дослідження. Були окреслені майбутні напрями досліджень у цій галузі. Ці напрями забезпечили основу для подальшого дослідження еволюції штучних створінь у віртуальних біоценозах і появи передових можливостей спілкування та співпраці. Ці досягнення містять потенціал для підняття штучного життя та штучного інтелекту на новий рівень розуміння та можливостей.
Наукові основи, деякі результати та перспективи моделювання еволюційно обумовленого ноогенезу штучних створінь у віртуальних біоценозах
Keywords: agent-based modeling; artificial life; artificial intelligence; growing neural networks; evolution; noogenesis; evolutionary design; агентне моделювання; штучне життя; штучний інтелект; зростаючі нейронні мережі; еволюція; ноогенез; еволюційний дизайн